Адаптивная система управления предприятием в кризисных условиях - Хаустова, Ирина Евгеньевна (НТУ "ХПИ", 2017)
Сущность понятия адаптивного управления определена как управленческая деятельность, организованная в взаимосвязанный комплекс действий субъектов функционирования, направленный на поддержание уровня конкурентоспособности посредством реализации механизма управления инновационными процессами на основе наблюдения за состоянием системы управления. Рассмотрены функции системы адаптивного управления. Проанализированы основные показателям качества для системы управления предприятием.

The essence of the concept of adaptive management is defined as management activity organized in an interconnected complex of actions of the subjects of functioning aimed at maintaining the level of competitiveness of the ability through the implementation of the mechanism of management of innovation processes on the basis of monitoring the state of the management system. The functions of the adaptive control system are considered. The main quality indicators for the enterprise management system are analyzed. The main quality indicator for the control system is accuracy, reliability, stability, ease of use by the manager, the optimal number of hierarchical levels.
Adaptive management system in the crisis
Keywords: адаптация; конкурентоспособность; стратегическое управление; управленческие решения; методы имитационного моделирования; enterprise; management; adaptation; adaptive management system; competitiveness